A Study of Buyer Motivations at the Bottom of Pyramid in Urban India - Ritu Srivastava; Vibhava Srivastava
The Indian bottom of pyramid (BoP) segment contributes around 85% of the total national household market. This study attempts to ascertain the purchase behaviour of customers at the Indian urban BoP. It endeavours to appreciate the viewpoint of the urban BoP consumers in the purchase process with reference to their purchase basket comprising of products mainly across categories such as grocery, perishables and basic consumer durables. The study starts with qualitative grounded theory followed by quantitative survey-based approach. It presents and validates emergent themes to give insights about purchase behaviour of consumers at urban BoP. The empirical findings of the study discovered five consumer motivations through factor analysis. The subsequent result of the cluster analysis showed that the urban BOP market is heterogeneous. Since the size of cluster is substantial, companies must make marketing efforts to target them on a priority basis. The study proposes a conceptual model of consumer motivation supported by the self-determination Theory for the urban BoP market in India.